Dissociation Is Associated with Emotional Maltreatment in a Sample of Traumatized Women with a History of Child Abuse. Issue 1 (1st January 2015) - Haferkamp, Lisa; Bebermeier, Anke; Möllering, Andrea; Neuner, Frank
Abstract : Theories of dissociation emphasize that symptoms of dissociation are correlated with traumatic events. Although the association of dissociative symptoms and retrospective reports of child abuse with a focus on mainly sexual and physical abuse has been well documented, investigation of the contribution of emotional or psychological types of maltreatment to the prediction of dissociation has been neglected to a great extent. The aim of this study was to determine the differential impact of different types of maltreatment on dissociative symptoms in a sample of 203 female residential patients treated for posttraumatic stress disorder linked to child maltreatment. Moreover, it was examined whether the link between dissociation and child maltreatment is direct or indirect. Subjects completed questionnaires on child maltreatment, posttraumatic stress, and dissociative symptoms. Although all types of maltreatment were related to dissociative symptoms, emotional abuse was the strongest and most direct predictor of dissociation in multivariate hierarchical analyses with the influence of other trauma types being confounded by emotional abuse. This study highlights the importance of emotional types of maltreatment for the genesis of dissociative symptoms in patients with posttraumatic stress disorder.